N-Acetyl-l-Cysteine Supplement in Early Life or Adulthood Reduces Progression of Diabetes in Nonobese Diabetic Mice. Issue 4 (28th November 2018) - Argaev Frenkel, Lital; Rozenfeld, Hava; Rozenberg, Konstantin; Sampson, Sanford R; Rosenzweig, Tovit
ABSTRACT: Background: Oxidative stress contributes to the pathologic process leading to the development, progression, and complications of type 1 diabetes (T1D). Objective: The aim of this study was to investigate the effect of the antioxidant N -acetyl-l -cysteine (NAC), supplemented during early life or adulthood on the development of T1D. Methods: NAC was administered to nonobese diabetic (NOD) female mice during pregnancy and lactation, and the development of diabetes was followed in offspring. In an additional set of experiments, offspring of untreated mice were given NAC during adulthood, and the development of T1D was followed. Morbidity rate, insulitis and serum cytokines were measured in the 2 sets of experiments. In addition, markers of oxidative stress, glutathione, lipid peroxidation, total antioxidant capacity and activity of antioxidant enzymes, were followed. Results: Morbidity rate was reduced in both treatment protocols. A decrease in interferon γ, tumor necrosis factor α, interleukin 1α, and other type 1 diabetes-associated proinflammatory cytokines was found in mice supplemented with NAC in adulthood or during early life compared with control NOD mice. The severity of insulitis was higher in control NOD mice than in treated groups. NAC administration significantly reduced oxidative stress, as determined by reduced lipid peroxidation and increased total antioxidant capacity in serum and pancreas of mice treated in early life or in adulthood and increased pancreatic glutathione when administrated in adulthood. The activity of antioxidant enzymes was not affected in mice given NAC in adulthood, whereas an increase in the activity of superoxide dismutase and catalase was demonstrated in the pancreas of their offspring. Conclusion: NAC decreased morbidity of NOD mice by attenuating the immune response, presumably by eliminating oxidative stress, and might be beneficial in reducing morbidity rates of T1D in high-risk individuals.